Country in which or from which the employee carry out her/his work in the light of Article 8.2 Regulation Rome I. Commentary to the judgment of the CJEU of 15 July 2021, joined cases C-152/20 and C-218/20 - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The judgment in question is a response to questions referred for a preliminary ruling by a Romanian court which has to decide on the law applicable to the minimum wage to be paid to a number of Romanian workers. The Court of Justice answers two joined cases in which the employees work in a State other than that the State whose law is applicated. Under Article 8 of the Rome I Regulation, the law applicable to the individual employment contract is the law chosen by the parties -Romanian law in our case- and the mandatory provisions of the law which would be applicable in the absence of choice, provided that they are more protective to the employee. The law that would be applicable if the parties had not chosen Romanian law as the law governing their contractual relationship is that of the State in which the employee habitually carries out his work (Art. 8.2 IRR) -Italy and Germany, in the two joined cases. In the CJEU, the Court concludes that the provisions on minimum wages can be considered to be stipulations that cannot be excluded by agreement, mandatory provisions, therefore, and provides that it is up to the referring judicial body to assess whether this regulation of the State in which the employee habitually carries out his work is more favourable to the employee than that of the State whose law is applicated. In this case, the latter should be the one applicable to the particular question of the minimum wage, since it is more protective of the employee.
Keywords: individual employment contract; country in which of from which employee habitually carry out her o his work; provisions which cannot be derogated from by agreement; minimum wage